Identify and prioritise the critical factors in implementing the reverse logistics practices: a case of Indian auto component manufacturer. (2017) - Luthra, Sunil; Mangla, Sachin Kumar; Kumar, Sanjay; Garg, Dixit; Haleem, Abid
In recent years, reverse logistics (RL) practices have been perceived a great recognition among researchers/practitioners. In this paper, we intend to identify and prioritise the critical factors (CFs) in implementing the RL practices, from the industrial viewpoint. There are 13 CFs crucial in accomplishing the RL practices were recognised on the basis of critical review of literature and experts opinion. These finalised 13 CFs were then analysed to determine their priority by means of analytical hierarchy process (AHP) technique. The AHP technique assists in determining the relative importance of the identified RL implementation critical factors. The findings of the work may help managers to address the related issues in RL implementation. Inputs needed to carry out this research work are taken from an Indian automotive components manufacturing company. The results of the study may help researchers/practitioners to prioritise their efforts to implement RL practices in effective manner. In the end, sensitivity analysis is carried out to examine the proposed RL implementation CFs stability.